Gene Expression Analysis Reveals Age and Ethnicity Signatures Between Young and Old Adults in Human PBMC - Hu, Yang; Xu, Yudai; Mao, Lipeng; Lei, Wen; Xiang, Jian; Gao, Lijuan; Jiang, Junxing; Huang, Li`an; Luo, Oscar Junhong; Duan, Jinhai; Chen, Guobing (Frontiers in Aging, 2022)
Human immune system functions over an entire lifetime, yet how and why the immune system becomes less effective with age are not well understood. Here, we characterize peripheral blood mononuclear cell transcriptome from 132 healthy adults with 21–90 years of age using the weighted gene correlation network analyses. In our study, 113 Caucasian from the 10KIP database and RNA-seq data of 19 Asian (Chinese) are used to explore the differential co-expression genes in PBMC aging. These two dataset reveal a set of insightful gene expression modules and representative gene biomarkers for human immune system aging from Asian and Caucasian ancestry, respectively. Among them, the aging-specific modules may show an age-related gene expression variation spike around early-seventies. In addition, we find the top hub genes including NUDT7, CLPB, OXNAD1, and MLLT3 are shared between Asian and Caucasian aging related modules and further validated in human PBMCs from different age groups. Overall, the impact of age and race on transcriptional variation elucidated from this study may provide insights into the transcriptional driver of immune aging.